دور الدين في تاريخ الحضارات عند ابن خلدون، ومالك بن نبي، وأرنولد توينبي: (The Role of Religion in the History of Civilizations in the View of Ibn Khaldūn, Mālik bin Nabi, and Arnold Toynbee) - Belmoumene, Mohamed Fadel; Bin Mohd Nor, Mohd Roslan (Online Journal of Research in Islamic Studies, 2025)
ABSTRACT/ملخص: تعرض هذه الورقة موقف ثلاثة مفكرين في الفكر الحضاري وعلم الاجتماع الإنساني من قضية "الدين" ودوره في الحضارات الكبرى وتطور الفكر البشري عبر العصور، وهم حسب الترتيب الكرونولوجي: ابن خلدون (1332-1406م)، أرنولد توينبي (1889-1975م)، مالك بن نبي (1905-1973م). تبدأ هذه الورقة بنظرة عامة حول فكرة دور الدين في حركة البشر والتاريخ والحضارات من خلال مفكرين وفلاسفة غربيين وشرقيين، في محاولة للإجابة على الإشكال الذي كثيراً ما يُطرح وهو: ما فائدة الدين عل المستوى الحضاري؟ وهل فوائد الدين متعلقة بالحياة الروحية فقط؟ وهل مازلنا نحتاج إلى الدين بعد هذا الرشد البشري الذي وصلنا إليه؟ وللإجابة على حزمة الأسئلة السابقة تم عرض موقف عبد الرحمن ابن خلدون من دور الدين من خلال مصطلح "العصبية"، وموقف مالك بن نبي من خلال مصطلح "الفكرة الدينية"، وموقف أرنولد توينبي من خلال مفهوم "العجلة والمركبة"، وذلك بالاعتماد على المنهج التاريخي والتحليلي، وتنتهي الورقة إلى أنّ للدين -بمفهومه العام- دوراً مهما في مناح مختلفة من حركة الحضارات كظهور الدول، وانبثاق الفلسفات، وصعود العلوم والاكتشافات. ABSTRACT This paper presents the position of three thinkers in civilizational thought and human sociology on the issue of "religion" and its role in major civilizations. And they are, in order: Ibn Khaldun (1332-1406), Arnold Toynbee (1889-1975), Mālik Binnabi (1905-1973). This paper begins with an overview of the idea of the role of religion in the movement of history and civilizations through Western and Eastern thinkers, in an attempt to answer the question that is often raised, like: What is the benefit of religion at the level of civilization? Are the benefits of religion related to spiritual life only? Do we still need religion after this human maturity that we have reached? In order to answer the previous questions, the paper presented the position of Ibn Khaldūn on the role of religion through the term “’asabiyyah”, the position of Mālik through the term “The Religious Idea”, and the position of Arnold Toynbee through the concept of “The Wheel and the Vehicle” based on the historical and analytical approach. The paper concludes that religion - in its general sense - has an important role in various aspects of life, such as the rise of states, the emergence of philosophies, sciences and discoveries.